Erythema multiforme: A retrospective study of etiologies, clinical manifestations, and treatments - GÜNGÖR, TUĞÇE; GÜMRÜ TARÇIN, BİRSAY (My University, 2024)
Background/purpose: Erythema multiforme (EM) is considered a hypersensitivity reaction associated with drugs and infections, and remains underestimated due to the lack of precise classification and diagnostic criteria. The aim of this study was to evaluate the triggering factors and clinical manifestations of EM and to present our experience in the diagnosis and management of this disorder. Materials and methods: All patient records were reviewed, and records of patients admitted, diagnosed, and treated with EM were retrieved. Data on age, gender, medical history, triggering factor(s), clinical form, mucosal/cutaneous involvement, affected oral site(s), recurrence, and treatment were collected. The data were analyzed statistically at a significance level set at P 0.05). Conclusion: The results of this study, based on the data from 36 EM patients with oral involvement treated at our clinic, can guide dentists in this regard and may be considered as an epidemiological source for the region.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; General Dentistry; Clinical manifestation; Erythema multiforme; Management; Triggering factors